Quorum Sensing-Independent Cellulase-Sensitive Pellicle Formation Is Critical for Colonization of Burkholderia glumae in Rice Plants - Kwak, Gi-Young; Choi, Okhee; Goo, Eunhye; Kang, Yongsung; Kim, Jinwoo; Hwang, Ingyu (Frontiers in Microbiology, 2020)
Bacteria form biofilms as a means to adapt to environmental changes for survival. Pellicle is a floating biofilm formed at the air–liquid interface in static culture conditions; however, its functional roles have received relatively little attention compared to solid surface-associated biofilms in gram-negative bacteria. Here we show that the rice pathogen Burkholderia glumae BGR1 forms cellulase-sensitive pellicles in a bis-(3′-5′)-cyclic dimeric guanosine monophosphate (c-di-GMP)- and flagellum-dependent, but quorum sensing (QS)-independent, manner. Pellicle formation was more favorable at 28°C than at the optimum growth temperature (37°C), and was facilitated by constitutive expression of pelI, a diguanylate cyclase gene from B. glumae, or pleD, the GGDEF response regulator from Agrobacterium tumefaciens. Constitutive expression of pelI or pleD raised the levels of c-di-GMP, facilitated pellicle formation, and suppressed swarming motility in B. glumae. QS-defective mutants of B. glumae formed pellicles, while flagellum-defective mutants did not. Pellicles of B. glumae were sensitive to cellulase but not to proteinase K or DNase I. A gene cluster containing seven genes involved in bacterial cellulose biosynthesis, bcsD, bcsR, bcsQ, bcsA, bcsB, bcsZ, and bcsC, homologous to known genes involved in cellulose biosynthesis in other bacteria, was identified in B. glumae. Mutations in each gene abolished pellicle formation. These results revealed a positive correlation between cellulase-sensitive pellicles and putative cellulose biosynthetic genes. Pellicle-defective mutants did not colonize as successfully as the wild-type strain BGR1 in rice plants, which resulted in a significant reduction in virulence. Our findings show that cellulase-sensitive pellicles produced in a QS-independent manner play important roles in the interactions between rice plants and B. glumae.